Association between Hemorrhagic Stroke and Diabetes Mellitus; A Hospital-Based Case-Control Study - Tawhid, Mohammad Homayun; Habib, Khatera (Journal for Research in Applied Sciences and Biotechnology, 2023)
Introduction: Stroke is the third leading cause of death in the world. Numerous studies show that diabetes mellitus is one of the risk factors for stroke. In general, stroke is divided into two types: hemorrhagic & ischemic, and approximately 15-25% of strokes are the hemorrhagic type. Objective: As it is claimed that diabetes mellitus is an important risk factor for hemorrhagic stroke, this study attempts to explain the association between diabetes and hemorrhagic stroke. Method and Data Collection: According to Epi Info statistic software; 102 participants who were 40≥ years old, and had a hemorrhagic stroke in their brain CT scan or MRI, were selected as cases, and 255 Participants without having a hemorrhagic stroke, including as controls. The proportional distribution of cases and controls in terms of sex and age was considered. Data has been obtained primarily through the design of a questionnaire from admitted patients in the neurosurgery and neurology wards of Aliabad university hospital. Results: Out of 357 participants, 181 (50.7%) participants were female and 176 (49.3%) were male. The study found that 25.5% of the participants in the case group, and 13.3% of the participants in the control group, were exposed to diabetes mellitus. Considering (P-Value = 0.006) and Odds ratio (OR=2.224; 95% CI = 1.253 – 3.945), the association between hemorrhagic Stroke and diabetes mellitus is suggested to be significant. Conclusion: As a result of the study, we can claim that among other risk factors, Diabetes Mellitus can also be considered a possible predisposing factor for Hemorrhagic Stroke and there is a significant association between Hemorrhagic stroke and Diabetes mellitus.